Artificial light at night alters progression of cold neuropathy in a sex-dependent manner in a mouse model of type II diabetes mellitus - Bumgarner, Jacob R.; White, Rhett C.; Brown, Jordan A.; Nelson, Randy J. (Frontiers in Photonics, 2024)
Artificial light at night (ALAN) is a pervasive circadian rhythm disruptor. Exposure to ALAN is associated with detrimental effects on physiology and behavior, including disrupted metabolism, immune function, endocrine function, and pain behavior. Given the detrimental effects of ALAN and other circadian rhythm disruptors on pain, we sought to understand how ALAN may alter the progression and severity of diabetic neuropathy. To do this, we used a previously reported high-fat diet and streptozotocin injection protocol to induce a type II diabetic phenotype in ~8 week old female and male mice and then exposed the mice to either control or ALAN lighting conditions in 14:10 h light-dark cycles for four weeks. Male mice housed in control conditions exhibited reduced responsiveness to cold pain; in contrast, ALAN blunted this effect in male mice. ALAN exposure also elevated blood glucose and altered body mass loss in male mice. These effects were not present in female mice. The results of this study highlight the need to consider and study ALAN exposure and sex as a biological variable as risk factors in the treatment and mitigation of pain.